2013
DOI: 10.1039/c3ta12113e
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the effect of Si doping on the performance of SrFeO3−δ SOFC electrode materials

Abstract: In this paper we report the successful incorporation of silicon into SrFeO 3Àd perovskite materials for potential applications as electrode materials for solid oxide fuel cells. It is observed that Si doping leads to a change from a tetragonal cell (with partial ordering of oxygen vacancies) to a cubic one (with the oxygen vacancies disordered). Annealing experiments in 5% H 2 /95% N 2 (up to 800 C) also showed the stabilization of the cubic form for the Si-doped samples under reducing conditions, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 62 publications
4
50
1
Order By: Relevance
“…Therefore, one can conclude that the maximum solubility of silicon in 25. This is larger than x m = 0.15 in work [20]. However, the observed difference can be explained as a consequence of the higher synthesis temperature used in the present study.…”
Section: Resultscontrasting
confidence: 62%
See 3 more Smart Citations
“…Therefore, one can conclude that the maximum solubility of silicon in 25. This is larger than x m = 0.15 in work [20]. However, the observed difference can be explained as a consequence of the higher synthesis temperature used in the present study.…”
Section: Resultscontrasting
confidence: 62%
“…6. The results obtained by authors [20] in air at 800°С are also shown for comparison. One can see a good correspondence of the data.…”
Section: Transport Propertiesmentioning
confidence: 87%
See 2 more Smart Citations
“…[ 115 ] The cubic structure of SrFeO 3-δ was stabilized effectively by doping Si into the B-site of the oxide under a reducing atmosphere, making it a potentially useful anode material. [ 115 ] The cubic structure of SrFeO 3-δ was stabilized effectively by doping Si into the B-site of the oxide under a reducing atmosphere, making it a potentially useful anode material.…”
Section: Srfeo 3-δ -Based and Srcoo 3-δ -Based Oxidesmentioning
confidence: 99%